General anesthesia: Is it safe for newborns, infants and young children? - Nancheva, Jasminka; Kamnar, Viktor; Nancheva, Andrea; Georgieva, Daniela; Georgiev, Antonio; Andonovski, Alan (Association of medical doctors "Sanamed" Novi Pazar, 2016)
The exposure of neonates, infants and small children to general anesthesia is becoming a common occurrence. Accumulating preclinical data indicate that exposure to commonly used general anesthetic agents during key periods of brain development in this population(between late gestation and 3 to 4 years of age,) can lead to apoptotic neurodegeneration, synapse loss, and cognitive and neurobehavioral deficits that persist as the organism matures. New work suggests that infants and small children undergoing some types of surgery could have better recovery if they receive regional anesthesia rather than general anesthesia. In response to this concerns, the Food and drug administration (FDA) and the International Research Society in anesthesia (IARS) started an initiative called Smart Tots (Strategies for Mitigating Anesthesia- related neuro Toxicity in Tots) which examine the effects of anesthesia on brain development. Also another two major prospective studies are ongoing in children : PANDA (Pediatric Anesthesia Neurodevelopment assessment Study )project is a large, multi-center study based at the Morgan Stanley Childrens Hospital of New York at Columbia University, and another one is GAS study which is a multisite randomized controlled trial comparing neurodevelopment outcomes in infant receiving general anesthesia compared to spinal and other regional anesthetics to the stress response to surgery. The findings from these studies will help researches to design the safest anesthetic regimens and to develop the new and safer anesthetic drugs for use in pediatric medicine.